The role of pathology in an investigation of an outbreak of West Nile encephalitis in New York, 1999. - Shieh, W J (Centers for Disease Control and Prevention, 2000)
An outbreak of encephalitis occurred in New York City in late August 1999, the first caused by West Nile virus in North America. Histopathologic and immunopathologic examinations performed on human autopsy materials helped guide subsequent laboratory and epidemiologic investigations that led to identification of the etiologic agent.